2021
DOI: 10.1016/j.jval.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cost-Effectiveness Studies of Interventions With a Personalized Nutrition Component in Adults

Abstract: Important links between dietary patterns and diseases have been widely applied to establish nutrition interventions. However, knowledge about between-person heterogeneity regarding the benefits of nutrition intervention can be used to personalize the intervention and thereby improve health outcomes and efficiency. We performed a systematic review of cost-effectiveness analyses (CEAs) of interventions with a personalized nutrition (PN) component to assess their methodology and findings. Methods: A systematic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 100 publications
(420 reference statements)
1
6
0
1
Order By: Relevance
“…The strategy of improving patients' nutritional status to improve health and cost outcomes is well-known and gaining evergrowing supportive evidence. In a recent systematic review, Galekop et al identified 53 studies that analyzed the cost-effectiveness of personalized nutrition in patient care [39]. Nearly half of the analyses (49%) concluded that nutritional intervention was cost-effective, and 75% of the incremental cost-utility ratios were cost-effective given a willingness-to-pay threshold of USD 50,000 per quality-adjusted life-year [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of improving patients' nutritional status to improve health and cost outcomes is well-known and gaining evergrowing supportive evidence. In a recent systematic review, Galekop et al identified 53 studies that analyzed the cost-effectiveness of personalized nutrition in patient care [39]. Nearly half of the analyses (49%) concluded that nutritional intervention was cost-effective, and 75% of the incremental cost-utility ratios were cost-effective given a willingness-to-pay threshold of USD 50,000 per quality-adjusted life-year [39].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, Galekop et al identified 53 studies that analyzed the cost-effectiveness of personalized nutrition in patient care [39]. Nearly half of the analyses (49%) concluded that nutritional intervention was cost-effective, and 75% of the incremental cost-utility ratios were cost-effective given a willingness-to-pay threshold of USD 50,000 per quality-adjusted life-year [39]. Other researchers performed a specific value analysis on the use of nutritional support therapy to lower the risk of hospitalacquired infections (HAIs), which are life-threatening and expensive to treat [40].…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of conducting cost-effectiveness analyses for health innovations was first introduced in 1977 [19], it was not until recently that professional organizations proposed integrating cost-effectiveness/value assessments directly into clinical guidelines [20]. A recent systematic review evaluating the cost-effectiveness of personalized nutrition interventions did not find any studies that included genotype approaches [21]. Lack of economic studies can make it challenging to justify integrating NGx testing within patient care.…”
Section: Innovation Attributesmentioning
confidence: 99%
“…In this context a correct nutrition is one of the cornerstones of preventive and curative medicine (Singh et al , 2017). Moreover, it is believed that better health outcomes can be achieved for each euro spent guaranteeing the population an adequate nutritional intake (Galekop et al , 2021). The report published by the International Obesity Task Force shows that malnutrition in Europe is constantly increasing and, in some areas, it reaches the same percentages registered in the USA (Lobstein et al , 2005).…”
Section: Introductionmentioning
confidence: 99%